Nilai-Nilai Kearifan Lokal Tradisi Ruwahan Desa Sindangsari - Banjarsari Kabupaten Ciamis - Neli Rahmawati; Yat Rospia Brata; Agus Budiman; Sudarto Sudarto (Universitas Galuh, 2023)
This study aims to determine the implementation and reveal the values of local wisdom in the Ruwahan Tradition in Sindangsari Village, Banjarsari District, Ciamis Regency. The method used in this study is historical qualitative, namely 1) heuristics, 2) criticism, 3) interpretation, and 4) historiography. Besides that, it also uses the Anthropological Method, a Socio-Cultural research method (culture domain), by using triangulation or several methods when collecting and analysing analyses simultaneously (observations, interviews, literature studies, and field notes). The data collection used in this research is 1) a Literature Study and) a Field Study. The results of this study indicate that the Ruwahan Tradition is still being preserved to this day. At the same time, the local wisdom values of the Ruwahan Tradition can be seen from the Relationship between Humans and humans (hablum minannas), Human Relations with Nature (hablum minalalam), Human Relations and God (hablum minallah). The benefit of this research is as information material about the Ruwahan Tradition in Sindangsari Village, Banjarsari District, Ciamis Regency, and it is hoped that the community will feel proud and continually preserve it as a local cultural entity in a region.